Construction of Mn0.5Zn0.5Fe2O4 modified TiO2 nanotube array nanocomposite electrodes and their photoelectrocatalytic performance in the degradation of 2,4-DCP - Pan, J.; Li, Xin Yong; Zhao, Q.; Li, T.; Tade, Moses; Liu, Shaomin (Royal Society of Chemistry, 2015)
An ultrasound-assisted impregnation deposition technique was adopted to construct Mn0.5Zn0.5Fe2O4 nanoparticles on TiO2 nanotube arrays (NTAs) which were prepared by electrochemical anodization in a hydrofluoric acid system. The Mn0.5Zn0.5Fe2O4 nanoparticles were found to successfully deposit on the surface of the highly oriented TiO2 NTAs causing no damage to the ordered structure of the nanotubes. The as-prepared Mn0.5Zn0.5Fe2O4/TiO2 NTAs exhibited much improved photoelectrochemical capability. Compared with pure TiO2 NTAs, a more than 2.36-fold enhancement in photo-current density and a 2.17-fold enhancement in photo-conversion efficiency of the Mn0.5Zn0.5Fe2O4/TiO2 NTAs were achieved. The photoelectrocatalytic (PEC) activities of Mn0.5Zn0.5Fe2O4/TiO2 NTAs were evaluated by the degradation of toxic 2,4-dichlorophenol (2,4-DCP) in aqueous solution under simulated sun light irradiation. The experimental results indicated that the heterostructure photoelectrode showed much higher PEC activity than the pure TiO2 NTAs for the degradation of 2.4-DCP under simulated sun light irradiation. In addition, electron spin resonance examination confirmed that the photogenerated active species (˙OH and ˙O2−) were involved in the PEC degradation of 2,4-DCP. A mechanism accounting for the enhanced PEC activity of the Mn0.5Zn0.5Fe2O4/TiO2 NTAs was proposed. The enhanced PEC activity of the nanocomposite electrode could be attributed to the synergistic effects between the lowered electron–hole recombination rate by the applied bias and the wider spectral response promoted by the Mn0.5Zn0.5Fe2O4 component.